2009
DOI: 10.1002/14651858.cd004009.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Intrarectal quinine versus intravenous or intramuscular quinine for treating Plasmodium falciparum malaria

Abstract: We detected no difference in the effect on parasites and clinical illness for intrarectal quinine, but most trials were small. Pain may be less with intrarectal proprietary, buffered quinine preparations (made less acidic by adjustment of the pH to 4.5). Further larger trials in patients with severe malaria and in adults are required before the intrarectal route can be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Seven studies in African children that evaluated quinine administered with a loading dose by the IV or IM route were identified [ 10 - 16 ]. In addition, three studies identified by a Cochrane review but on African children not strictly having severe malaria were included [ 17 ]. These studies compared the effectiveness of quinine administered with a loading dose by the rectal (IR) and the IV route [ 18 , 19 ] and the IR and the IM route [ 20 ] (Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies in African children that evaluated quinine administered with a loading dose by the IV or IM route were identified [ 10 - 16 ]. In addition, three studies identified by a Cochrane review but on African children not strictly having severe malaria were included [ 17 ]. These studies compared the effectiveness of quinine administered with a loading dose by the rectal (IR) and the IV route [ 18 , 19 ] and the IR and the IM route [ 20 ] (Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Time to regain consciousness was 36-39 h [19]. A recent systematic review and metaanalysis however, concluded no significant difference in PCT, FCT, mortality rate, duration of hospitalization, and time-to-drinking between IR and IM administration [56], but not for the effect of dosage.…”
Section: Childrenmentioning
confidence: 94%
“…Antimalarial drugs can be administered in a number of ways: oral (amodiaquine), intramuscular (artemether), intravenous (artesunate) [ 143 ]. There is also a scope for rectal administration of the antimalarial drug (quinine) [ 144 ].…”
Section: Application Of Thermosensitive Liquid Suppositories As Innovative Systems For Delivering Various Drugsmentioning
confidence: 99%